Kinematics of fault-propagation folding: Analysis of velocity fields in numerical modeling simulations. (September 2022) - Plotek, Berenice; Heckenbach, Esther; Brune, Sascha; Cristallini, Ernesto; Likerman, Jeremías
Abstract: Fault-propagation folding occurs when a shallow fold is created by an underlying propagating thrust fault. These structures are common features of fold and thrust belts and hold key economic relevance as groundwater or hydrocarbon reservoirs. Reconstructing a fault-propagation fold is commonly done by means of the trishear model of the forelimb, a theoretical approach that assumes simplistic rheological rock properties. Here we present a series of numerical models that elucidate the kinematics of fault-propagation folding within an anisotropic sedimentary cover using complex visco-elasto-plastic rheologies. We explore the influence of different parameters like cohesion, angle of internal friction, and viscosity during folding and compare the velocity field with results from the purely kinematic trishear model. In the trishear paradigm, fault-propagation folding features a triangular shear zone ahead of the fault tip whose width is defined by the apical angle that in practice serves as a freely tunable fitting parameter. In agreement with this framework, a triangular zone of concentrated strain forms in all numerical models. We use our models to relate the apical angle to the rheological properties of the modeled sedimentary layers. In purely visco-plastic models, the geometry of the forelimb obtained can be approximated using a trishear kinematic model with high apical angles ranging between 60° and 70°. However, additionally accounting for elastic deformation produces a significant change in the geometry of the beds that require lower apical angles (25°) for trishear kinematics. We conclude that all analyzed numerical models can be represented by applying the theoretical trishear model, whereby folds involving salt layers require high apical angle values while more competent sedimentary rocks need lower values. Highlights: Numerical models were performed to produce fault-propagation folds over an anisotropic sedimentary cover. The velocity field during deformation was obtained. Our results were compared with the trishear theoretical kinematic field. A triangular region of concentrated strain evolved in all numerical models. The geometry of the forelimb obtained can be approximated using a trishear kinematic model with high apical angles. The incorporation of elastic deformation in the numerical models produced a significant change in the geometry of the beds.